Effect of pH of Supporting Electrolyte on Boron Adsorption by Some Soils of Punjab - Arora, Harsh; Bhardwaj, S.S.; Sharma, B.D. (Asian Journal of Chemistry, 2010)
Adsorption is one of the most important processes affecting the availability of boron in soils. Boron adsorption on soil constituents is dependent on solution pH. Therefore, the effect of pH on boron adsorption by 12 soils from well defined soil series of Punjab was studied at varying pH of supporting electrolyte solutions of NaCl and CaCl2· The adsoption of boron increased with increase in pH up to 8 or 9 and thereafter the adsorption decreased with increase in pH in most of the soils. However, in some of the soils, there was an increase in boron adsorption with inerease in pH over the entire range of pH (5–11) in the presence of CaCl2 only.